Ego depletion: Applications and implications for auditing research. Issue 1 (October 2015) - Hurley, Patrick J.
Abstract: In this paper, I synthesize the prior psychology literature on ego depletion and apply this literature to an auditing setting. Ego depletion refers to a reduced desire or ability to use self-control in task performance due to using self-control on prior tasks. I focus on the likely causes and consequences of depletion in an auditing setting, as well as means of mitigating depletion and recovering self-control resources. While ego depletion theory is prevalent in the psychology literature, little is known about whether or how ego depletion affects professionals on meaningful task performance. As a result, this synthesis is aimed at stimulating future ego depletion research in accounting, and specifically auditing, by surveying existing literature and applying this literature to an auditing setting. Further, I develop 13 questions for future research to investigate. My synthesis reveals that ego depletion likely has a pervasive effect in an auditing setting, and can hinder auditors' judgment and decision-making (JDM) quality. Therefore, this synthesis helps to provide a greater understanding of the impact of auditing tasks on individuals, and refines both auditor JDM and ego depletion theories.